2020
DOI: 10.1177/2045894020917887
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and fluid challenge during right heart catheterisation for evaluation of dyspnoea

Abstract: This prospective study compared exercise test and intravenous fluid challenge in a single right heart catheter procedure to detect latent diastolic heart failure in patients with echocardiographic heart failure with preserved ejection function. We included 49 patients (73% female) with heart failure with preserved ejection function and pulmonary artery wedge pressure ≤15 mmHg. A subgroup of 26 patients had precapillary pulmonary hypertension. Invasive haemodynamic and gas exchange parameters were measured at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
1
5
0
2
Order By: Relevance
“…This study found a correlation of both methods for distensibility, but we still consider iCPET as indispensable because this correlation becomes blurred if the healthy control subjects in this study are omitted. This is in line with our own findings [ 16 ] that exercise and fluid challenge activate different pathophysiological pathways and unmask diastolic dysfunction in different patient groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study found a correlation of both methods for distensibility, but we still consider iCPET as indispensable because this correlation becomes blurred if the healthy control subjects in this study are omitted. This is in line with our own findings [ 16 ] that exercise and fluid challenge activate different pathophysiological pathways and unmask diastolic dysfunction in different patient groups.…”
Section: Discussionsupporting
confidence: 93%
“…All catheter procedures were performed in hospitalized patients and followed the guidelines of the ESC/ERS [ 14 ] and German recommendations [ 15 ]. We have published the detailed course of the exercise RHC previously [ 16 ]. In brief, this procedure starts with a hemodynamic measurement at rest in a supine position (labelled in the following “baseline”) and a second measurement at rest in a semi-supine position (“45° at rest”), followed by unloaded cycling in a semi-supine position for 3 to 5 min (“unloaded cycling”), and 3 to 5 min cycling at 25 W. If both anaerobic threshold (in the literature, synonymously “first ventilatory threshold”) was not reached and dyspnea reported was only mild to moderate, a 50 W step was appended.…”
Section: Methodsmentioning
confidence: 99%
“…An exercise RHC with a simultaneous measurement of oxygen uptake was performed in patients with a suspected multifactorial etiology of dyspnea, based on the findings of the preceding noninvasive examinations (echocardiography, CPET, and body plethysmography). We previously published a detailed description of the exercise RHC procedure 3 . Briefly, the procedure began with the measurement of hemodynamic parameters at rest with the patient in the supine position (0°); a second measurement of hemodynamic parameters was performed at rest with the patient in a semi‐supine position (45°).…”
Section: Methodsmentioning
confidence: 99%
“…We previously published a detailed description of the exercise RHC procedure. 3 Briefly, the procedure began with the measurement of hemodynamic parameters at rest with the patient in the supine position (0°); a second measurement of hemodynamic parameters was performed at rest with the patient in a semi‐supine position (45°). CO was next measured during unloaded cycling in a semi‐supine position for 3–5 min (45° at 0 W), and finally during 25‐W exercise in a semi‐supine position for 5 min; in some cases, patients underwent exercise with intensity exceeding 50 W. The level of exercise in the final step corresponded to 58 ± 19% of the maximum oxygen uptake (peakVO 2 ) achieved by the patient during cycle ergometry in the sitting position, performed on average 12 days beforehand.…”
Section: Methodsmentioning
confidence: 99%
“…Die Nutzung des PVR setzt die Messung des PCWP (eine valide Messung unter Belastung ist an eine Reihe von Konditionen gebunden, wie Druckaufnehmer in Höhe des mittleren Thorax, Mittelung über mehrere Herzschläge, keine Durchführung von Atemmanövern u. a. m.) voraus, wobei es kaum Konsens zur altersabhängigen oberen Grenze dieses Wertes gibt [143]. Nach Durchsicht der Literatur haben wir uns für einen Grenzwert von 20 mmHg als "oberen Normalwert" bei körperlicher Belastung entschieden [144].…”
Section: Vorschlag Für Eine Erweiterung Des Bisherigen Icpet-algorithmusunclassified